The concept and implementation of common link theory in hadith research - Shaffat, Idri; Ahmad Maghza Rizaka (Technium Social Sciences Journal, 2024)
This study discusses the concept and implementation of the common link theory developed by G.H.A. Juynboll in hadith research. Through a qualitative approach and using the library research method, this study discusses Juynboll’s views and works related to hadith and outlines the steps of isnād and matn analysis used in the implementation of the common link theory. In isnād analysis, the study identifies common links and partial common links in order to trace the historical origins of a particular hadith. While in the matn analysis, the study compares hadith texts with similar themes to determine the authentic parts. The case study of the hadith on “The Virtue of Conveying the Prophet’s Word” reveals the central role of a narrator in the transmission of the hadith, with the results of the isnād and matn analyses supporting Juynboll’s common link theory. As a result, this study contributes to the academic understanding of hadith criticism, especially in facing Orientalist doubts about the validity of hadith.